ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEMISKINAN DENGAN METODE REGRESI PROBIT ORDINAL (Studi Kasus Kabupaten/ Kota di Jawa Tengah Tahun 2013) - Alin Citra Suardi; Triastuti Wuryandari; Sugito Sugito (Jurnal Gaussian, 2016)
According to BPS, Central Java is third in terms of the number of poor people in Indonesia. The overall number of poor people in Central Java in 2013 was 4.811.300 inhabitants. Factors that influence the level of poverty can be derived from the employment factor, economic factors, or educational factors. Based on these three factors independent variables were selected which supposed to influence the poverty level. There are inflation, City Minimum Wage by Regency/City, Gross Regional Domestic Product at constant market prices, Unemployment Rate, Mean Years of Schooling, and Illiteracy Rate. The poverty level is categorized into three categories. There are Prosperous, Medium and Poor. The independent variables were analyzed its effect on poverty levels that have been categorized by the Ordered Probit Regression method. The complete model of the ordered probit regression is tested the significance of the parameters by likelihood ratio test and Wald test. Based on ordered probit regression analysis, variables that affect the level of poverty in Central Java in 2013 was Inflation, City Minimum Wage by Regency/City, and Mean Years of Schooling (MYS).Keywords : Poverty Level, Central Java, Ordered Probit Regression.